How Does Environmental Information Disclosure Affect Corporate Environmental Performance? Evidence from Chinese A - Share Listed Companies - Lin, Zehao (International Journal of Energy Economics and Policy, 2025)
Global climate change and air pollution pose serious threats to economic growth and public welfare, creating urgent challenges for sustainable development. Corporations, as key agents in resource utilization and pollution control, are increasingly scrutinized for their environmental strategies and transparency. This study employs a two-way fixed effects panel model using data from Chinese A-share listed companies between 2015 and 2021 to investigate the impact of environmental information disclosure (EID) on corporate environmental performance, as well as its regional heterogeneity and underlying mechanisms. The empirical results reveal that EID significantly enhances environmental performance, and this effect is particularly pronounced in cities with high population density and limited green space. Mechanism analysis suggests that EID improves performance mainly through optimizing resource allocation and improving financial structures. These findings provide robust evidence that environmental disclosure can serve as an effective governance tool to promote corporate sustainability and regional environmental quality, offering policy implications for strengthening disclosure regulations and supporting targeted regional strategies.